The dilemma of flood occurrence in Accra: climate change or poor land use planning and practices? - Amaglo, Jedidiah Nusinyo; Takyi, Stephen Appiah; Asibey, Michael Osei; Amponsah, Owusu; Mensah, Henry (SN Social Sciences, 2022)
Over the years, climate change and land use planning are considered debateable perspectives on the true cause of the perennial flooding in many African cities, with inconclusiveness on the subject matter. This paper thus contributes to the debate with trend analysis on which of the two perspectives is the major cause of the perennial flooding situation in African cities, taking Accra as a study case. The focus of this paper is therefore to examine the nature of flooding to succinctly draw a justified conclusion on the deliberations regarding whether flooding in Accra is caused by climate change or land use planning. The paper achieves this using the case study research design with data drawn from both primary and secondary sources, specifically, review and synthesis of relevant literature and interviews with state agencies and 100 households. The findings showed variations in responses on the major cause of flooding—climate change and weak enforcement of land use planning. However, most households (52%) and all agency officials, supported by climate change-flood occurrence data revealed that floods in Accra are mostly human induced. Due to population growth, the city has expanded onto wetlands and flood-prone areas, thus distracting the natural flow of water. This paper, therefore, supports the school of thought that the flooding occurrence in Accra, among others, is caused by poor and uncoordinated land use planning efforts which is as a result of several institutional constraints. A well-maintained physical development such as the protection of wetlands by city authorities will go a long way to minimise the perennial occurrence of flood events and the associated impacts.